Sexual health needs and psychosocial well-being of patients with prostate cancer in a regional cancer Center. (13th September 2020) - Preyde, Michèle; Kukkonen, Tuuli; Cunningham, Craig
ABSTRACT: Prostate cancer is the most common cancer for men. The cancer diagnosis and treatment can affect patients' psychosocial and sexual health. The purpose of this research project was to identify the sexual health concerns of patients with prostate cancer. An anonymous survey was administered to patients while accessing Grand River Regional Cancer Center (GRRCC) that included measures of sexual health and perceived stress and social support, ratings for preferred modes of sexual health programming, and open-ended questions on sexual health and masculinity. Seventy-five patients completed the survey; their mean age was 73.9 years (SD 7.2), the majority were in a couple relationship and identified as heterosexual. The concerns most endorsed were physical changes in sexual functioning and being able to satisfy their partner sexually. These findings can inform sexual health programming and psychosocial oncology for men with prostate cancer.